2018
DOI: 10.1155/2018/6061395
|View full text |Cite
|
Sign up to set email alerts
|

Basosquamous Carcinoma: A Single Centre Clinicopathological Evaluation and Proposal of an Evidence-Based Protocol

Abstract: Basosquamous carcinoma (BSC) is an uncommon skin malignancy with significant invasive and metastatic potential. There are currently no clear management guidelines. This study evaluates the management and outcomes of patients diagnosed with BSC over a 7-year period. We present an evidence-based unit protocol for the management of BSC. All patients treated for BSC between 2009 and 2015 were reviewed. Data collected included patient demographics, tumour-specific information, management strategy, presence of recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…It is also well established that BSC occurs more frequently in men 21 , 25 . Our study reflects similar results—male patients constituted 57%.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…It is also well established that BSC occurs more frequently in men 21 , 25 . Our study reflects similar results—male patients constituted 57%.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, desmoplastic and adenosquamous SCCs are highly infiltrative, have a high risk of local recurrence, metastasis, and death 29 . Some authors believe that BSC is a variant of BCC, whereas others have suggested that BSC behaves more aggressively like SCC 21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations